2014
DOI: 10.4028/www.scientific.net/amm.680.77
|View full text |Cite
|
Sign up to set email alerts
|

Grain and Feature Size Effect on Material Behavior for Micro-Sheet-Forming

Abstract: Negligible factors in bulk materials, such as grain-size effects, have proven inappropriate to be neglected for micro-forming processes. Studies had shown that material behavior varies greatly with the increasing of the scale in the micro-forming world. Therefore, in every micro-forming-related process, especially in micro-stamping, studies and analyses of each material used for the process have to be considered as indispensable in order to be able to understand their behavior and to be able to correlate their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In the micro-forming world, studies have demonstrated that material behavior differs dramatically as the scale is increased. As a result, in any microform-related process, particularly microstamping, studies and analyses of each material used in the process must be considered essential to understand their behavior and associate their behavior with the process [18].…”
Section: Limitations Of Micro-formingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the micro-forming world, studies have demonstrated that material behavior differs dramatically as the scale is increased. As a result, in any microform-related process, particularly microstamping, studies and analyses of each material used in the process must be considered essential to understand their behavior and associate their behavior with the process [18].…”
Section: Limitations Of Micro-formingmentioning
confidence: 99%
“…This impact is entirely dependent on the material's average grain size and is most significant in macro-scale materials. Despite their thinness, the examined strips can still be classified as macro-scale material due to their relatively substantial width and length [18].…”
Section: Limitations Of Micro-formingmentioning
confidence: 99%